PENGARUH CITA RASA, DESAIN DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN GELAS ALE-ALE - Dwito Resky ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
The title of this research is the Influence of Taste, Design and Promotion on Purchasing Decisions of Ale-Ale Glass Drinks in Padang Kapuk Village, Manna City District. This research is motivated by purchasing decisions which are always fluctuating and different for each individual. Purchasing decisions can be influenced by several factors. These factors are estimated to be Taste, Design and Promotion. This study aims to analyze the influence of taste, design and promotion on the decision to purchase ale-ale glass drinks in the village of Padang Kapuk, District of Manna City.The object of this research is the consumers of Ale-Ale glass drinks who live in Kelurahan Padang Kapuk, Kota Manna. The population in this study is not known with certainty, therefore the sampling method refers to the statement of Hair et al., (2010). So that the number of respondents or samples in this study were obtained as many as 100 samples. The data collection method uses a questionnaire with the help of Google Form.By using multiple linear regression data analysis techniques, the results of this study can be concluded that the Taste variable has a positive and significant effect on purchasing decisions, Design has a positive and significant effect on purchasing decisions and Promotion has a positive and significant effect on purchasing decisions for Ale-Ale glass drinks in the Kelurahan Padang Kapuk, Manna.Keywords: Taste, Design, Promotion and Purchase Decision